Investigating the spatiotemporal changes and driving factors of nighttime light patterns in RCEP Countries based on remote sensed satellite images - Li, Jie; He, Suling; Wang, Jinliang; Ma, Weifeng; Ye, Hui (Journal of cleaner production, 2022)
The Regional Comprehensive Economic Partnership (RCEP) agreement signed in November 2020 is the world's largest and greatest potential free trade area. It was officially enforced on January 1, 2022, which attracted great worldwide attention. The RCEP advocates for the development of the low-carbon economy but lacks effective monitoring methods for socioeconomic conditions and carbon emissions. Nighttime light (NTL) images can objectively reflect socioeconomic status and carbon emission potential. However, most studies focused only on consistency correction for multi-source NTL data without deeply analyzing NTL dynamics. An in-depth analysis of the NTL change in the RCEP region is necessary and will strongly facilitate the strategic deployment of a low-carbon economy in RCEP countries. Sen's slope estimator, the Mann-Kendall trend test, the Mann-Kendall mutation test, and Hurst analysis were adopted to analyze the spatiotemporal changes of NTL in the past and future, and gray relational analysis was applied to explore driving factors. The results showed that (1) RCEP's NTL became brighter from 2000 to 2018, and the total NTL amount in 2018 was 3.27 times that in 2000. NTL in all countries except Japan showed an increasing trend to varying degrees, and this trend was more pronounced in developing countries. The maximum increase amount and growth rate were in China and Vietnam, respectively. (2) Areas where NTL showed an increasing trend in the past accounted for 76.67% of the NTL zones, and the areas where predicted to be brighter in the future accounted for 63.87%. These regions were generally clustered in developed urban zones. However, most Japanese cities have observed darkening trends. (3) The relational grade between NTL and all socioeconomic factors in the RECP region was greater than 0.6, and construction land expansion was the most direct and profound driver. Compared with that in developed countries, NTL in developing countries was more closely related to socioeconomic factors. Spatiotemporal Changes and Driving Factors in Nighttime Light for the RCEP Region. [Display omitted] •Nighttime light (NTL) in the RCEP region became brighter from 2000 to 2018.•NTL in developed cities increased significantly and is expected to be brighter.•China led the lighting trend, while Japan's NTL declined.•Construction land expansion was the dominant driver of NTL changes in RCEP region.•Socioeconomic factors in developing countries more strongly promoted NTL increases.